2016
DOI: 10.1002/brb3.478
|View full text |Cite
|
Sign up to set email alerts
|

Methylene blue and normobaric hyperoxia combination therapy in experimental ischemic stroke

Abstract: IntroductionIschemic stroke is a global burden that contributes to the disability and mortality of millions of patients. This study aimed to evaluate the efficacy of combined MB (methylene blue) and NBO (normobaric hyperoxia) therapy in experimental ischemic stroke.MethodsRats with transient (60 min) MCAO (middle cerebral artery occlusion) were treated with: (1) air + vehicle (N = 8), (2) air + MB (N = 8), (3) NBO + vehicle (N = 7), and (4) NBO + MB (N = 9). MB (1 mg/kg) was administered at 30 min, again on da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 53 publications
0
5
0
1
Order By: Relevance
“…A novel example of this combined normobaric hyperoxia treatment with MB. Combination therapy decreased infarct volume and yielded behavioral improvements in a stroke model beyond that of either treatment alone [56]. Our work found that the addition of MB to therapeutic hypothermia managed to rescue neuronal cell death and behavioral outcomes after extended GCI.…”
Section: Methylene Blue Mitochondrial Dysfunction and Neurodegenementioning
confidence: 79%
“…A novel example of this combined normobaric hyperoxia treatment with MB. Combination therapy decreased infarct volume and yielded behavioral improvements in a stroke model beyond that of either treatment alone [56]. Our work found that the addition of MB to therapeutic hypothermia managed to rescue neuronal cell death and behavioral outcomes after extended GCI.…”
Section: Methylene Blue Mitochondrial Dysfunction and Neurodegenementioning
confidence: 79%
“…The foot fault score of the foot fault test was determined to evaluate walking ability at 41 days after induction brain inflammation, as described previously (Rodriguez et al, 2016). The rat was placed on an elevated, grid floor (34 mm×29 mm) for 2 min.…”
Section: Methodsmentioning
confidence: 99%
“…For example, recent studies showed that NBO extended neuro-and vaso-protection of N-acetylcysteine in transient focal ischemia (Liu et al, 2016), combination of NBO and melatonin demonstrated more protective effect on reperfusion injury through regulation cerebral microcirculation (Beker et al, 2015). In addition, combination therapy of NBO with methylene blue improved functional outcome and reduced infarct volume compared to either treatment alone and these improvements extended up to 28 days (Rodriguez et al, 2016).…”
Section: Combination Treatment With Nbomentioning
confidence: 99%